Chart Showing the Production of Anthracite Coal in the Lehigh, Schuylkill, and Wyoming Regions; Anthracite, Bituminous, and Char¬coal Pig Iron in the United States, And Petro¬leum in Pennsylvania, from 1820 To 1876 - John Henry Harden (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1877)
IT appears that in the earlier days of anthracite coal mining, 1824-25, the Lehigh region mined 76 per cent. of all the coal sent to market. During the same period Wyoming sent 12 and 5 per cent. respectively, whilst the Schuylkill sent 11 and 18 per cent., the number of tons marketed being in those days very small indeed. In the year 1828 the Schuylkill region mined over one-half of all the coal sent to market, and continued to do so for thirty years (with the exception of the year 1831), until 1858 ; since that date the pro¬duction has declined very steadily in comparison with the other regions, until, in 1876, it was only 34 per cent. Wyoming, in the year 1820, was mining 40 per cent., but the production of all the regions was very small ; in six years it declined to 5 per cent., increased to 34 per cent. in 1831, declined to 10 per cent. in 1838. Since which time the increase has been gradual, until 1873-75 Wyoming produced over 50 per cent. of all the anthracite coal sent to market. In 1867 the production exceeded that of Schuylkill, and has continued to do so since that time. In the year 1876, during the existence of the " coal combination," Wyoming lost 9 per cent. ; during the same time Lehigh gained 7 and Schuylkill 2 per cent. over their relative production of the preceding year, the decrease of Wyoming being two and a half million tons, the increase of the Lehigh one million, the decrease of the Schuylkill nearly three-quarters of a million. The extraordinary production of the Lehigh region at a time of decreased demand and in opposition to an agreement with the other regions to limit the supply to the supposed demand was the cause of the disagreement which ultimately broke up the combination of the great coal-producing and carrying companies. The Lehigh region produced very steadily, from 1829 to 1854, an average of about 22 per cent. of the whole production. From 1854